Ecology and structural violence: The South African reception of Lutheran voices from North America - Conradie, Ernst (Nederduitse Gereformeerde Teologiese Tydskrif, 2015)
This review essay offers an assessment of two recent monographs by Larry Rasmussen and Cynthia Moe-Lobeda in the field of ecotheology. It focuses on the category of moral vision that both authors employ. It shows how the notion of critical moral vision helps to identify and assess the root causes of economic inequalities and ecological destruction in terms of structural violence, structural evil and the very nature of sin. It also explains why such moral vision forms the key but by itself remains insufficient for social transformation. The influence of such insights in the South African context is illustrated with reference to teaching and research done at the University of the Western Cape and, more specifically, the category of transfiguration in Desmond Tutu’s theology.